Development Of A Five-Tier Diagnostic Test Instrument On Atomic Structure Material To Identify Misconceptions Of SMA Negeri 2 Medan Students. - Dalimunthe, Makharany; Surabika Br Tarigan, Anjany Tasya (Universitas Lampung, 2023)
This study aims to 1) determine the results of the needs analysis, 2) the feasibility level of the Five-Tier instrument, 3) the percentage of misconceptions, and 4) student responses. The subjects in this research were 36 students of grade X MIPA 6 SMA Negeri 2 Medan. The instrument was validated by 5 expert validators, namely 3 chemistry lecturers and 2 chemistry teachers. This research uses the development method (R &; D) with a 4D model (Define, Design, Development, and Disseminate). This research shows 1) the needs analysis stated that students needed a Five-Tier diagnostic test instrument, 2) the eligibility level met the qualifications well with an assessment from five validators, the reliability test was 0.68, 3) the percentage of the atomic structure misconception category was 27%, 4) students responded well with an average of 66.7% DOI: 10.23960/jppk.v12.i3.2023.09